Integration of Neo-Sufism in the Social Welfare Education Curriculum in Indonesian Islamic Universities - Budi Rahman Hakim; Fajrur Rahman (FKIP, Universitas Palangka Raya, 2023)
This study aims to investigate the integration of Neo-Sufi values ​​into the Social Welfare Education curriculum in Indonesian Islamic universities. The focus of the study includes the relevance of the Neo-Sufi ethical-spiritual framework to graduate competencies, as well as an analysis of curriculum documents, conceptual models, and academic discourse. The research employs a qualitative method with a systematic literature review design, drawing from indexed scientific articles, academic regulations, and curriculum syllabi from three state Islamic universities. The findings indicate that values ​​such as empathy, justice, sincerity, and social service are implicitly present but are not yet systematically structured within the curriculum design. No operational pedagogical model was found that explicitly references Neo-Sufism. The main conclusion asserts that the integration of Neo-Sufism into the curriculum represents a transformative opportunity to develop graduates who are not only professionally competent but also spiritually grounded. Future curriculum development should include explicit modules and pedagogical strategies rooted in Sufi values.